Identification of lattices from genus of compact surface - De Carvalho, Edson Donizete [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2006)
In this work we propose procedures for the identification of structure of group associate lattices from fundamental region F4g of regular tessellations {4g; 4g} in the Euclidian plane and hyperbolic plane, where g denote genus of compact surface. © 2006 SBrT.
Keywords: Hyperbolic spaces; Lattices codes; Quaternion ordem; Regular tessellations; Symmetries groups; Intelligent vehicle highway systems